Electroanalysis of solid particles - Lin, Q (2017)
This thesis reports theoretical and experimental work with the primary aim of developing new electrochemical methods to detect and characterise solid particles at the micron scale, specifically alumina (aluminium oxide) particles and graphene nanoplatelets, as representative of insulating and conductive particles, respectively. The fundamentals of thermodynamics, kinetics and mass transport in electrochemistry are introduced in Chapter 1, with the elaboration of electrodes, voltammetry and chronoamperometry used for electroanalysis. A comparison of non-electrochemical and electrochemical techniques used to analyse solid particles is also given. Chapter 2 provides information on both the experimental procedures and theoretical simulations used in the studies. Chapter 3 first investigates the oxidation of catechol (1,2-hydroxybenzene) in the pH range from 1.0 to 14.0 voltammetrically using a clean glassy carbon electrode. Analysis of the voltammograms allows the inference of the reaction mechanism in full and kinetics using a "scheme of squares". When the electrode surface is covered with sparse coverages of alumina particles, strong apparent catalysis of the reaction is discovered. The cause of such an apparent catalysis is then examined in Chapter 4. Comparison of the voltammograms at alumina- and graphene nanoplatelets-modified electrodes reveals that a change in the thermodynamics of the intermediate species, rather than a change of electron transfer rate, results in the apparent electrocatalysis of the redox process. With understanding of the oxidation of catechol electrocatalysed by alumina-modified electrodes, Chapter 5 reports to innovative "tagging" of catechol onto the surface of alumina. A new electrochemistry method based on particle impacts is used to quantify the adsorption of catechol on single alumina particles. In these experiments, particles suspended in solution impact a microelectrode held at a suitable potential for the oxidation or reduction of the adsorbed species. The current "spikes" induced from the impacts can be simulated to derive information such as the size of the particles, the surface coverage of modifiers, and the diffusion coefficients of charge transfer over the surface of the particles. The method is further applied to various modifiers, including 9,10-anthraquinone, tetrachloro-1,4-benzoquinone, and poly(vinylferrocene) in Chapter 6. The investigation of solid particles then proceeds from alumina to graphene nanoplatelets. In Chapter 7, graphene nanoplatelets are "tagged" with a ferrocene derivative prior to impact experiments. Two types of charge transfer are involved in the impacts: Faradaic due to redox of the modifier, and capacitative due to disruption of the electrical double layer at the electrode/solution interface. For the first time, both processes can be observed during the impacts of graphene nanoplatelets. Chapter 8 exploits the impacts method to evaluate the electron transfer rate of the ferrocene/ferrocenium redox couple immobilised on graphene nanoplatelets in aqueous solution. Single graphene nanoplatelets modified with poly(vinylferrocene) are allowed to impact a microelectrode. By adopting the potential applied, each graphene nanoplatelet temporarily acts as a "chemically modified nanoelectrode" for the duration of the impact, facilitating the resolution of fast electron transfer for the redox couple. Finally, Chapter 9 demonstrates the use of poly(vinylferrocene)-modified graphene nanoplatelets as a mediator for the oxidation of l-cysteine in aqueous solution. The theory of catalytic particle impacts is developed. The kinetics and mechanism of the catalysis is then assessed harnessing both experiment and theory.